Penapisan Kesehatan Mental melalui Edukasi dan Skrining Depresi, Stress dan Kecemasan (DASS-42) pada Masyarakat di Kelurahan Grogol - Anastasia Ratnawati Biromo; Alexander Halim Santoso; Farell Christian Gunaidi; Juan Edbert; Louis Anthony (Jurnal Pengabdian Bidang Kesehatan, 2025)
Mental health disorders such as depression, stress, and anxiety are commonly found among individuals in productive age and can have a substantial impact on their quality of life, both personally and socially. Early symptoms like fatigue, mild anxiety, or sleep disturbances, often go unrecognized as they frequently perceived as minor issues, leading to many cases remained undiagnosed during the early stages. The Community Service Program (PKM) conducted in Grogol Subdistrict aimed to raise the public awareness of the importance of early detection of mental health issues through screening using the Depression Anxiety Stress Scale (DASS-42). This activity adopted the Plan-Do-Check-Act (PDCA) approach, encompassing mental health education, standardized screening, and follow-up in the form of referrals to mental health professionals for participants with abnormal scores. Among 67 participants, 6 individuals (8.96%) were found to have mild to severe depressive symptoms, 19 individuals (28.36%) exhibited mild to severe anxiety symptoms, and 2 individuals (2.99%) experienced mild stress symptoms. These findings emphasized the vital role of early education and screening in preventing mental health disorders, also serves as a foundation for fostering sustained public awareness regarding the importance of maintaining psychosocial well-being.